SRI SOUNDHIRA PANDEESWARAR TEMPLE- A HISTORICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
The daughter of Soundhira Pandian, who came from the Veera Marthanda Varman dynasty that made Kalakad the capital, had a chronic mental illness. It was incurable by anyone and did not require treatment. The king declared that whoever cured his illness would be given her in marriage and half the kingdom. At that time, a person from Kerala, who was on his way to Kasyatri, came this way, met the king, and cured his daughter's illness. That Anthana, who refused the king's daughter and the kingdom, built a temple in the northern part of the area near a Thirukula where elephants crawl, and then advised the king to consecrate and worship the idol of Nataraja, who had lost his right to come here. As told by Kerala Anthana, King Soundhira Pandian built a beautiful big temple, consecrated Sri Soundhira Pandeeswarar and Gomati Ambal there, and waited for Sthapathi's arrival. One day, when Sthapathi, who had lost his right, came there, the king was pleased to see him and immediately ordered him to make an image of Nataraja. Even with the loss of his right hand, the talented Sthapathi fitted the wood blocks and, with their help, carved a magnificent statue of Nataraja, more beautiful than before. Enchanted by the beauty of the statue, Sthapati tried to caress its right cheek, and with the grace of Lord Shiva, his right hand grew, and he immediately merged into the kingdom of Shiva. The idol with the pinched scar was placed in the Shiva temple at Karvelankulam. Sthapathi's pinch scar can still be seen on the Utsava statue. Thalavirutcham of the temple is the Nelly tree.